Manfaat Trimetazidine Dalam Tatalaksana Pasien Chronic Coronary Syndrome Dengan Stable Angina - Aldy Dion; Edgar Bezaliel Hartanto (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2022)
Cardiovascular Disease (CVD) has resulted in the deaths of 17.9 million individuals in 2016, representing 31% of the global death. Coronary Artery Disease is a spectrum of CVD with a clinical manifestation called Chronic Coronary Syndrome (CCS). Stable angina is the main symptom of CCS that threatens patient safety. This paper aims to convey the in-depth benefits of Trimetazidine as an effective and safe pharmacological option for CCS patients with stable angina. This paper is a narrative review type literature study using the literature review method regarding the benefits of Trimetazidine (TMZ) for CCS patients with stable angina. As many as 16 references from research journal articles, case reports, and international guidelines are used. The analysis showed that administration of TMZ caused a significant frequency reduction of weekly angina attacks from 4.7 ± 3.5 to 2.2 ± 2.4 in the first month (p <0.001) and to 0.9 ± 1.3 in the third month (p <0.001). The decrease in weekly nitroglycerin consumption was -3.23, 95% CI: -4.23 to -2.24 (p <0.0001). The CCS classification of patients increased from 83% of patients classified in CCS class II or III to 32% after being given TMZ. There were no significant differences between the three doses of TMZ (3 × 20 mg, 2 × 35 mg, and 1 × 80 mg). TMZ has been reported to cause few mild side effects in patients. In general, the use of TMZ as monotherapy or in combination can improve the condition of CCS patients with stable angina.